The prevalence and general health status of people with intellectual disabilities and autism co‐occurring together: a total population study. Issue 4 (28th November 2018) - Dunn, K.; Rydzewska, E.; MacIntyre, C.; Rintoul, J.; Cooper, S.‐A.
Abstract: Background: Little is known about the population prevalence of co‐occurring intellectual disabilities and autism, and its impact on general health status. The study aimed to investigate this, in comparison with the general population. Method: Whole country data from Scotland's Census, 2011, were analysed. Descriptive statistics were generated; chi‐squared tests were undertaken; and logistic regressions were undertaken both with the whole general population data, adjusted for age and gender, and within the population with co‐occurring intellectual disabilities and autism. Results: A total of 5709/5 295 403 (1.08/1000) people had co‐occurring intellectual disabilities and autism; 2.58/1000 children/young people and 0.74/1000 adults. The peak reported prevalence was at age 10 years (3.78/1000); 66.0% were male. Their general health status was substantially poorer than for the rest of the population, more so for children/young people, and they had more limitations in their day‐to‐day activities. Co‐occurring intellectual disabilities and autism had odds ratio = 48.8 (45.0–53.0) in statistically predicting poor health. Conclusion: This is the first study to report the population prevalence of coexisting intellectual disabilities and autism, and the substantial influence this double disadvantage has on general health status, apparent across the entire life course. This highlights a group in need of wider recognition for whom resources should be focused on and planned for, informed by evidence. Staff in services for people with either of these conditions need to be trained, equipped, resourced and prepared to address the challenge of working for people with this duality. This is essential, to address these substantial health inequalities.